Knowledge, attitude and practice regarding mother-to-child transmission of HIV, its prevention, and associated factors among antenatal women attending a health care facility in district Srinagar, North India: a cross sectional study - Mukhtar, Mohsina; Quansar, Ruqia; Bhat, Suhail N.; Khan, S. M. Salim (International Journal Of Community Medicine And Public Health, 2020)
Background: HIV pandemic still remains an issue of major concern on a global scale with more than 37.9 million people estimated to be living with HIV in 2019 globally -an increase from 36.7 million in 2015. India has the third largest HIV epidemic in the world, with 2.1 million people living with HIV, with higher prevalence among men (0.25%) than women (0.19%) out of which children (15 years) accounts for 6.54%, while two fifth (40.5%) of total HIV infections are among females. Methods: A cross-sectional hospital based study was conducted over a time period of 03 months and a total of 366 pregnant women attending the health care facilities of Block Hazratbal were included in the study. Results: Among the study participants, only 15 (4.1%) women had not heard about HIV/AIDS, 314 (85.8%) were aware of sexual transmission as a mode of transmission and only half of the study subjects (50.8%) knew about MTCT, more than half of the subjects (68.3%) were aware that the transmission of HIV infection can occur during pregnancy. Conclusions: Although the study population showed adequate knowledge about HIV infection, there was a considerable lack of knowledge regarding mother-to-child transmission of HIV infection and its prevention.